Assessment of failure and cohesive zone length in co-consolidated hybrid C/PEKK butt joint. (1st August 2018) - Baran, Ismet; Warnet, Laurent L.; Akkerman, Remko
Highlights: Failure mechanisms of co-consolidated C/PEKK skin-stiffener structure under bending. Material characterization of a 20% short fiber reinforced C/PEKK filler. Coupled XFEM with cohesive zone modelling. Unstable crack growth in the filler and delamination at the skin-filler interface. Critical assessment of the cohesive zone length development during delamination. Abstract: The failure mechanisms and the cohesive zone length (CZL) during fracture of a recently developed butt jointed thermoplastic composite are evaluated in this paper. The laminated skin and the web were made of AS4/PEKK. The butt joint (filler) was injection molded from 20% short AS4 filled PEKK. The skin and web were co-consolidated together with the filler to form a hybrid butt joint structure. The crack initiation and propagation in the filler and the delamination at the skin-filler interface were captured using a high-speed camera. It was found from the experimental observations that the crack initiated in the filler and then propagated towards the skin-filler interface in less than 33  μ s under three-point bending. A numerical model was developed using the finite element method in ABAQUS to predict the failure and CZL. The crack initiation and progression in the filler was predicted using the Virtual Crack Closure Techniques (VCCT) and the delamination at the skin-filler interface was modelled using the cohesive surfaces. The predicted stiffness of the specimen, the location of crack initiation and propagation as well as the force drop during delamination were in good agreement with experiments. The development of CZL was critically assessed and it was found that the CZL increases during mix mode delamination. The effect of interface strength and critical energy release rate on the CZL was investigated in the parameter analysis.